1,3-Bis(2-chlorobenzoyl)-3,4,5,6-tetrahydropyrimidine-2(1H)-thione - Yildirim, Sema Ozturk; Akkurt, Mehmet; Genc, Murat; Sekerci, Memet; Fun, H. -K. (Int Union Crystallography, 2006)
The title compound, C18H14Cl2N2O2S, was synthesized by the reaction of 1,4,5,6-tetrahydropyrimidine-2-thiol and 2-chlorobenzoyl chloride. The dihedral angle between the two chlorobenzene rings is 76.2 (1)degrees. The ring carbon ( and attached H atoms) opposite the C S group are disordered over two sites. In the crystal structure, there is one intermolecular C - (HO)-O-... and one intramolecular C - (HN)-N-... hydrogen bond.